Attachment Styles and Communication of Displeasing Truths - Sessa, Isora; D’Errico, Francesca; Poggi, Isabella; Leone, Giovanna (Frontiers in Psychology, 2020)
This work explores how humans manage the communication of a displeasing and face-threatening truth, and how thecommunicative strategies of the sender and the reaction of the receiver are influenced by their attachment style. Two experimental studies demonstrate that the attachment styles of both senders and receivers can influence the communicative styles of the sender, the emotions that both senders and receivers feel or attribute to their interlocutor, and the reactions of the receivers. In Study 1, couples of participants played a bogus computer game, ostensibly to test their abilities. Subsequently, ‘the spokesperson’ was given the task to communicate to the ‘the receiver’ a bogus low score of the other and a high score of oneself. Finally, all participants completed an adult Attachment Style Questionnaire (ASQ). A content analysis of the verbal messages of the spokespersons showed two main communication styles: frankness and mitigation. The results suggest that the spokespersons' attachment style influencesthese communication styles. Using a similar procedure, Study 2 showed that spokespersons with a high avoidant attachment more frequently used frankness when communicating low scores to the receivers. Furthermore, the emotions and impressions reported by anxious and avoidant spokespersons and receivers, respectively, confirm the negative model of the self or the other, typical, respectively, in anxious and avoidant attachment. The detection of communicative strategies stemming from different attachments styles might be of use in user modeling and the planning of personalized systems.